The effectiveness of a systems engineering course in developing systems thinking - Camelia, Fanny; Ferris, Timothy L. J.; Behrend, Monica B. (IEEE, 2019)
performance and affective engagement with ST assessment is proposed as an approach to assess students' ST in both domains. The results can support course change decisions and guide learning experience development. Background: SE education aims to produce graduates with strong knowledge and skills in SE and a strong appreciation of the practical value of ST, which addresses the cognitive and affective domains in education. Consequently, it is important to evaluate the effectiveness of SE courses in developing students' ST in these domains, an area that studies do not consider. Intended Outcomes: An understanding of the ST ability of undergraduate students in an SE course in a domain specific engineering program in both the cognitive and affective domains. Application Design: A study evaluated the effectiveness of two SE classes in developing students' ST capacity using a combined cognitive and affective assessment tool developed and validated in previous studies. ST assessment is determined by combining ST performance and affective engagement. To observe the transformation of students' ST capacity, a longitudinal design collected data at two times in each of two offerings of an SE course offered by the same university in two locations--Australia and Singapore. Findings: The course developed students in most dimensions of cognitive ST, but did not appear to improve students' affective engagement with ST.
Keywords: Affective domain; assessment tools; cognitive domain; student assessment; systems engineering education; systems thinking; undergraduate